Pengaruh Mekanisme Tata Kelola Perusahaan Terhadap Kinerja Perusahaan yang Dimoderasi oleh Kualitas Audit pada Perusahaan Keluarga yang Terdaftar di Bursa Efek Indonesia - Robin; Willy Kaslianto; Wibisono, Chablullah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The government, including Bank Indonesia, has taken many steps to encourage the implementation of GCG in the banking environment. In 2006, Bank Indonesia issued Bank Indonesia Law No. 8/4/PBI/2006 on 30 January 2006 on the implementation of GCG for commercial banks. This study is a type of quantitative research because it is a comparative case study where the cause and effect effect between the dependent variable and the independent variable can be found. The samples in this study are IDX-registered companies that have family ownership and operate in the non-financial sector. The purpose of the research used was the data available in the audited financial reports of the company listed on the IDX. A sample collection method is a sampling method that determines the sample through a variety of evaluations and specific requirements in order to maximize the data obtained for the experimenter. This study uses independent variables of board size, number of independent commissioners, number of commissioner and audit committee qualifications and audit quality as comparison variables. Based on the research, the researcher can conclude that the size of the board is positive and has a significant effect on the ROE, but has no effect on the Tobin's q. Independent commission has no effect on firm performance as measured by ROE and Tobin's q. Because special committees are supposed to work professionally to monitor the activities of the company's management, it can be difficult to access the necessary information. The number of commission points does not have a significant effect on firm performance as measured by ROE or Tobin's Q. This is because financial knowledge does not always come from formal education, but rather from practical experience. The audit committee does not have a significant impact on the company's performance as indicated by ROE or Tobin's Q. The fact that the audit committee in a company is created as one of the requirements for the company to meet the regulations of the Financial Services Authority (OJK). Accounting quality cannot moderate the effect of board size on corporate performance as shown by ROE and Tobin's Q. Audit quality cannot moderate the independent auditor's impact on firm performance as measured by ROE and Tobin's Q.